Utilitarismo extensional: el rol de la felicidad según J.S. Mill - Mesa Díez, David Santiago (Pontificia Universidad Católica del Perú, 2024)
This paper aims to show that the idea of happiness defended by John Stuart Mill is based on a notion of utility that must be understood in extensional terms. This means that, according to Mill, the idea of happiness does not subordinate other practical precepts—such as the ones of justice and freedom. Instead, these precepts build the set of rules that enable its realization. This approach of Mill, which I call “extensional utilitarianism”, allows me to highlight the fundamental role that happiness plays in the context of Mill’s practical philosophy.

En este artículo mi propósito es mostrar que la idea de felicidad que expone John Stuart Mill está basada en una noción de utilidad que debe entenderse en términos extensionales. Esto significa que para Mill la idea de felicidad no subordina a otros preceptos prácticos —como los de justicia y libertad—, sino que estos comprenden el conjunto de reglas que permiten su realización. Esta posición de Mill, que identifico como “utilitarismo extensional”, me permitirá indicar el rol destacado que ocupa la felicidad en el contexto de su filosofía práctica.
Extensional Utilitarianism: The Role of Happiness According to J.S. Mill
Keywords: J. S. Mill; Happiness; Utilitarianism; Pleasure and pain; Inductive empiricism; J. S. Mill; Felicidad; Utilitarismo; Placer y dolor; Empirismo inductivo; https://purl.org/pe-repo/ocde/ford#6.03.01